2022
DOI: 10.1080/07391102.2022.2095305
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Omicron SARS-CoV-2 RBD and other variants in their ability to interact with cell receptors and monoclonal antibodies

Abstract: SARS-CoV-2 has caused immeasurable damage worldwide and available treatments with high efficacy are still scarce. With the continuous emergence of new variants of the virus, such as Omicron, Alpha, Beta, Gamma, and Delta -the so-called variants of concern, the available therapeutic and prevention strategies had to return to the experimental trial to verify their effectiveness against them. This work aims to expand the knowledge about the SARS-CoV-2 receptor-binding domain (RBD) interactions with cell receptors… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 219 publications
2
21
0
Order By: Relevance
“…Comparisons of the binding affinities for the VOCs with other theoretical studies were reported by us in previous work. 11 For example, Golcuk and coauthors 52 recently also showed that the RBD-ACE2 binding affinity is strengthened for the Delta in comparison with the wt as seen by us. In their work, they identified an additional contribution from increased hydrophobic interactions.…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…Comparisons of the binding affinities for the VOCs with other theoretical studies were reported by us in previous work. 11 For example, Golcuk and coauthors 52 recently also showed that the RBD-ACE2 binding affinity is strengthened for the Delta in comparison with the wt as seen by us. In their work, they identified an additional contribution from increased hydrophobic interactions.…”
Section: Resultssupporting
confidence: 53%
“…119 The latter issue has been recently discussed in the literature. 11,64,119 On one hand, the model can capture larger discrepancies between different variants as for the comparison between Delta and Omicron/BA.1. On the other hand, differences for a single mutation can be within the estimated statistical error even when the reported experimental assays show a larger enhancement for the binding affinity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations